A New Look at Theory of Mind in Children with Ocular and Ocular-Plus Congenital Blindness. (January 2014) - Begeer, Sander; Dik, Marjolein; Voor De Wind, Marieke J.; Asbrock, Doreen; Brambring, Michael; Kef, Sabina
Introduction: Delays in theory of mind (ToM) of children who are congenitally blind have often been attributed to the absence of visual and social experiences. However, these delays could also be partly due to neural factors. In some children, the blindness itself has neural causes (ocular-plus blindness). Children whose blindness has an ocular-plus cause may be more delayed in ToM than children with blindness due to ocular causes. Methods: In the current study, performances of children with congenital ocular-plus blindness ( n = 22) and congenital ocular blindness ( n = 9) were compared with sighted children ( n = 103) on ToM tasks designed for children with blindness. Results: Compared with sighted children, ToM performance was delayed in children with ocular-plus blindness, but not in children with ocular blindness. Discussion: ToM development in children with congenital blindness could be related to factors other than the loss of a sensory function and the lack of visual social and communicative experiences. Implications for practitioners: The specific ToM deficits in children with ocular-plus blindness may help in developing new research paradigms that consider delays in ToM in children with congenital blindness.